2017
DOI: 10.1186/s40001-017-0260-2
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of thyroid dysfunction in an Iranian adult population: the predictor role of thyroid autoantibodies: results from a prospective population-based cohort study

Abstract: BackgroundThe prevalence of thyroid dysfunction is high in Isfahan, an area of iodine sufficient in Iran. The aim of this study is to investigate the incidence of thyroid dysfunctions in adults of metropolitan Isfahan and to determine the role of thyroid autoantibodies.MethodsIn a population-based cohort study in 2006–2011, we measured TSH, T4, T3, thyroid peroxidase antibody (TPOAb), and thyroglobulin antibody (TgAb) in 618 out of 2254 people who were euthyroid in 2006. The incidence rates per 1000 person-yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 50 publications
4
31
1
Order By: Relevance
“…Normal thyroid function was considered as 0.3 mIU/L ≤ TSH ≤ 3.6 mIU/L. The diagnosis of overt and subclinical hypothyroidism respectively was done based on TSH levels higher than 10 and 3.6 mIU/L < TSH ≤ 10 mIU/L [18]. Normal T4 levels were considered between 4.5 and 12.0 μg/dL for normal participants.…”
Section: Outcome Definitionmentioning
confidence: 99%
“…Normal thyroid function was considered as 0.3 mIU/L ≤ TSH ≤ 3.6 mIU/L. The diagnosis of overt and subclinical hypothyroidism respectively was done based on TSH levels higher than 10 and 3.6 mIU/L < TSH ≤ 10 mIU/L [18]. Normal T4 levels were considered between 4.5 and 12.0 μg/dL for normal participants.…”
Section: Outcome Definitionmentioning
confidence: 99%
“…Intriguingly, previous studies demonstrate the predictor role of thyroid antibodies. [25][26][27] In their 13-year follow-up cohort study, Walsh et al 26 concluded that TPO-Ab and TG-Ab in combination of thyrotropin provide the useful estimate of long-term risk of hypothyroidism. A 5-year follow-up study by Li Y et al 27 from China reported similar results.…”
Section: Discussionmentioning
confidence: 99%
“…Normal T4 levels were considered between 4.5 and 12.0 μg/dL for normal participants. T4 value lower than 4.5 was one of the additional criteria' for hypothyroidism patients [31]. The values higher than 40 and 100 IU/mL were considered positive for TPOAb and TGAb, respectively.…”
Section: Outcome Definitionmentioning
confidence: 99%